ANALISIS PUTUSAN MAHKAMAH KONSTITUSI NOMOR 65/PUU-XXI/2023 PERIHAL PENGUJIAN UNDANG-UNDANG NOMOR 7 TAHUN 2017 TERHADAP UNDANG-UNDANG DASAR 1945 TENTANG LARANGAN KAMPANYE DI TEMPAT PENDIDIKAN - Yosenda, Firminus R; Ratu Udju, Hernimus; Lawung, Mario A (Petitum Law Journal, 2025)
This study's objective is to investigate the ratio decidendi and legal implications of the Constitutional Court Decision Number 65/PUU-XXI/2023 concerning the constitutional review of Article 280 paragraph (1) letter h of Law Number 7 of 2017 on General Elections, particularly regarding the prohibition of campaigning in educational institutions. The Constitutional Court's ruling declared that the explanatory phrase of the article contradicts the 1945 Constitution and lacks binding legal force. This study uses a normative juridical approach and is analyzed qualitatively to reveal the Court's legal reasoning and its impact on the neutrality of educational institutions and legal certainty in election campaigns. The results show that the Court emphasizes the importance of maintaining the neutrality of educational spaces from practical political activities to protect the learning process and ensure justice and legal certainty in elections.